Analisis Kualitas Website Layanan Pengadaan Secara Elektronik Dengan Menggunakan Model WebQual 4.0 Pada Pemerintah Kabupaten Simalungun - Erwin Setiawan Panjaitan; Lihardo Rawaja Haloho; Salsalina Sembiring (Jurnal SIFO Mikroskil, 2018)
WebQual is one of the Web site quality-based Measurement methods, which have been contacted from WebQual 1.0 to WebQual 4.0. This study uses the WebQual 4.0 model, which corrects the three variables of usability, quality of information, and quality of quality website service interaction. This research aims to improve the quality of service website and government service of Simalungun Regency. The sample of the research is 42 people, where the sample location using sampling saturation. Data were collected through a questionnaire containing statements about user perceptions about the website. The data will be used to obtain the value of the WebQual Index used to determine the value of service quality. The result of the value of WebQual Index of each variable is usability is 0.85, the quality of information is 0.87 and the quality of service interaction is 0.86. Variables that most affect the quality of website services in general Simalungun District Government of the respondent is the variable quality of information with the WebQual Index of 0.87. Measurement Results WebQual Index shows that the quality of web service organizing electronically Simalungun District Government is very good with the value of Webqual Index of 0.86.